The Changes of T-Wave Amplitude and QT Interval Between the Supine and Orthostatic Electrocardiogram in Children With Dilated Cardiomyopathy - Tan, Cheng; Yi, Xiuying; Chen, Ying; Wang, Shuangshuang; Ji, Qing; Li, Fang; Wang, Yuwen; Zou, Runmei; Wang, Cheng (Frontiers in Pediatrics, 2021)
Objectives: Electrocardiogram (ECG) can be affected by autonomic nerves with body position changes. The changes of autonomic nerves excitation affect the process of cardiac depolarization and repolarization, and result in the changes of ECG waveforms. Materials and Methods: This was a prospective study. We investigated the changes of T-wave amplitude and QT interval between supine and orthostatic ECG in children with dilated cardiomyopathy (DCM). 64 children diagnosed as DCM were chosen as research group and 55 age- and sex-matched healthy children were chosen as control group. T-wave amplitude and QT interval in supine and orthostatic ECG were measured and differences of them were compared in both groups. Results: ①Comparisons between the supine and orthostatic ECG: Differences of T-wave amplitude in lead Ⅱ, Ⅲ, aVF and V5 and differences of QT interval in lead Ⅱ, aVL, aVF and V5 were lower in research group than in control group (P<0.05). ②Logistic regression analysis and diagnostic test evaluation: Difference of T-wave amplitude in lead Ⅲ has statistical significance for DCM diagnosis and when the value is 0.00 mV, the sensitivity and specificity were 39.7% and 92.6%. 3.Follow up: In the response group, the difference of T-wave amplitude in lead aVR increased and the difference of QT interval in lead V6 decreased after treatment (P<0.05). In the non-responsive group, there was no statistical difference between the differences of T-wave amplitude and QT interval between before and after treatment (P>0.05) Conclusions: The differences of T-wave amplitude and QT interval between supine and orthostatic ECG may have certain value for the diagnosis and prognosis of DCM in children.